STUDI BIOLEACHING LOGAM TANAH JARANG DARI RED MUD TAYAN, KALIMANTAN BARAT DENGAN MENGGUNAKAN JAMUR PENICILLIUM SP. - Akbar Sighab, Muhammad
Bauxite residue or red mud is an alkaline waste from the Bayer process. The need to process red mud is because red mud contains a lot of radioactive elements and is very alkaline so that it can cause various damage to the environment. In addition, red mud contains a complex of oxides of aluminum, iron, titanium, silicon and other valuable components that can be extracted. In this case, biohydrometallurgy is an environmentally friendly approach and requires low energy and costs. In this study, experiments will be conducted on the leaching of rare earth elements (REE) from red mud in Tayan, West Kalimantan.